Numerical simulation on fracture resistance and factors affecting toughness for welded joint of low-alloy steel. (January 2019) - Zhao, Longfei; Guo, Xiangyu; Cui, Haichao; Lu, Fenggui
Highlights: Crack propagation resistance curves of fracture toughness with different size specimens for welded joint were numerically simulated. The equivalent thickness for the plane strain fracture toughness B eq, is 11.5 mm for CrMoV steel based on simulation results. The depth of side groove, around 25% thickness of CT specimen, contributes to a smaller J integral distribution gradient near the crack front. Abstract: Crack propagation resistance for welded joint was numerically simulated by ABAQUS software, where compact tensile (CT) specimens with different thickness and depth of side groove were taken to discuss the variation and reliability of results. It is found that the critical fracture toughness J c increases with the thickness and then decreases gradually to the plane strain fracture toughness. The equivalent thickness B eq was put forward by numerical simulation. Strain energy density and the volume of plastic deformation zone were calculated to explain the effect of thickness on J c based on the theory of energy dissipation. The simulated results revealed that another critical geometry factor like the depth of side groove up to 25% of total thickness contributed to a smaller J integral distribution gradient. The CT specimen with suitable geometry size was obtained according to the numerical results, which helps in guiding the experimental test of fracture toughness. The simulation results of fracture resistance demonstrate a good consistency with experiments, showing that numerical model is of high reliability, and stable J c could be achieved at suitable specimen size. Graphical abstract: